HOSPITAL MORBIDITYINPATIENTS WITH CHRONICKIDNEYDISEASE STAGE UD - ShifrisІ.; Krot, V.; Gonchar, Y.; Krasyuk, E.; Dudar, I. (Ukrainian Journal of Nephrology and Dialysis, 2014)
According to opinion of European researchers the expenses, associated with in–patient treatment, constitutes the significant part of health service expenditure in population of patients on renal replacement therapy (RRT). Only in few studies the hospitalization levels were compared for population ofpatients on hemodialysis (HD) and peritoneal dialysis (PD). Aim. The aim of this study was analysis the hospital morbidity pattern in patients with CKD stage 5D on HD and PD. Materials and methods. It was performed the retrospective (for period 01 Jan to 31 Dec 2013) analysis of hospitalization structure and rate for patients, were treated by RRT. All hospitalization admissions were assessed in view of modality and duration of RRT, demographic/gender characteristics, and renal affection type. In 2013 the RRT treatment were provided to 351 patients, including the 296 on HD and 55 on PD. Results. Overall 173 cases of hospitalization were recorded, including 142 (82,08%) primary and 31 (17,92%) readmissions. Irrespective of RRT modality the three most common causes of hospitalization were cardiovascular diseases (CVD), bacterial infections, and anemia. 41 hospitalization was caused by RRT initiation (28 HD and 13 PD), the most of patients aged 45 years and older. The hospitalization rate in PD patients with was significantly higher than in patients on HD: 70,9±6,1% vs. 34,8±2,8%, respectively;p<0,0001. The duration of hospitalization was significantly higher by HD– than PD patients (30,09±17.21 vs. 21.82±10.56, respectively; p=0,0007). Conclusions. During follow–up, at least one hospitalization had more than 40%patients with CKD stage 5D. In HD patients the most common causes of hospitalization were bacterial infections, CVD and anemia. Anemia, CVD and bacterial infections were the most frequent causes hospitalization in PD patients.